The Loyalty Model of Private University Student - Leonnard, Leonnard; Daryanto, Heny K.S; Sukandar, Dadang; Yusuf, Eva. Z. (International Research Journal of Business Studies, 2014)
This study investigates Loyalty Model of Private University Student by using STIKOM London School of Public Relation as a study case. This study examined the model from service quality, college image, price, trust and satisfaction perspective. Thus, the objective of this study is to examine and analyze the effect of service quality, college image, tuition fee, trust and satisfaction towards students’ loyalty; the effect of service quality, college image, price and satisfaction towards trust; and the effect of service quality, college image and price towards satisfaction. This study used survey methodology with causal design. The samples of the study are 320 college students. The gathering of data is conducted by using questionnaire in likert scale. The analysis of the data used a Structural Equation Model (SEM) approach. The implication of this study is portraying a full contextual description of loyalty model in private university by giving an integrated and innovated contribution to Student Loyalty Model in private university.